Study on the Evolution Laws of Anchoring Property of Surrounding Rock of Argillaceous Weakly Cemented Roadway in Water Environment. (27th June 2022) - Zhang, Weiguang; Chang, Zhiguo; Bai, Jianbiao; Wang, Rui
Abstract : This paper is aimed at studying the influence of composition and microstructure on the Jurassic weakly cemented rock mechanical properties. No. 1802 tailentry was used as the engineering background, located in the Danan Lake No. 5 mine in Xinjiang, China. The weakly cemented sandstone compositions were analyzed by using X-ray diffraction instrument. And the microstructure was observed by using a scanning electron microscope. The uniaxial compression experiment was carried out to investigate the mechanical characteristics by using MTS mechanics experimental system, and the uniaxial compressive strength, Poisson's ratio, and elastic modulus were obtained. The relationships between the mechanical parameters that include the mineral composition, microstructural characteristics, uniaxial compressive strength (UCS), elastic modulus, cohesion, and friction angle of the weakly cemented sandstone and the water content were obtained. The attenuation of the anchorage force of the weakly cemented surrounding rock under different water-rich conditions was studied. The key reason of No. 1802 tailentry surrounding rock structure deterioration and roof fall was found. The model of a single anchor structure was established based on FLAC 3D to study the mechanical response of a single anchor structure under different water contents and the distribution and evolution laws of bearing stress field, effective compressive stress, and anchor axial force. The influences of parameters such as water content, pretightening force, and anchor length on the preload diffusion effect of weakly cemented surrounding rock anchorage structures are obtained. The key to controlling the deterioration of the surrounding rock structure of the weakly cemented entry is to reduce the water content of the roof. The research results provide reference for the control of the entry surrounding rock under similar stratum conditions.